THE EFFECT OF KNOWLEDGE MANAGEMENT AND TALENT MANAGEMENT ON ORGANIZATIONAL PERFORMANCE WITH ORGANIZATIONAL CULTURE AS A MEDIATING VARIABLE - Agustinus Setyawan (Universitas muhammadiyah malang, 2021)
This study aims to investigate the influence of knowledge management and talent management on organization performance and organizational culture as a mediating factor. This research uses methodology with an explanatory study by testing five hypotheses. A hundred twenty-seven managers from several coal companies in East Kalimantan Province are collected as a sample in this research. The researcher used the Smart PLS programs to examine the effect of the independent variable on the dependent variable through the mediating variable. The result of this study found that: (1) Knowledge management doesn’t affect organization culture; (2) Talent management practices affect organizational culture positively and significantly; (3) Knowledge management doesn’t affect organization performance; (4) Talent management affect organization performance positively and significantly; (5) Organization culture doesn’t affect organization performance; (5a) The mediation function of organizational culture is not significant between knowledge management and organizational performance, and (5b) The mediation function of organizational culture is not significant between talent management and organizational performance. This research has a managerial implication to guide the decision-maker in the company or manager in the human resource management to implement knowledge management, talent management, and organizational culture to improve organization performance.